PENGUKURAN PERMITIVITAS KOMPLEKS MATERIAL MAGNETIK MENGGUNAKAN METODE S-PARAMETER DENGAN PENDEKATAN NICOLSON ROSE-WEIR - Priyono, Priyono; Abidin, Nur; Nurhasanah, Iis (BERKALA FISIKA, 2019)
Dielectric properties of material are important properties because it describes the interaction of material with electromagnetic waves. The complex permittivity value of material is interesting because it can represent on how much energy savings and dissipation when the material gets exposed to electromagnetic waves. The aim of this paper was to determine complex permittivity by Nicolson-Ross-Weir (NWR) method. The NWR method was based on the phenomenon of reflection and transmission of electromagnetic wave that drip on materials. The values of the reflection coefficient (ï‡) and the transmission coefficient (T) were derived from reflection (S11) and transmission (S12) parameters. Determination of real permittivity in the frequency range of 10 GHz to 15 GHz of BaFe12O19 material was Îµ â€™ = 4.36 and Îµ â€ = 6.23. The second sample was BaFe9 (MnCo)1,5Ti1,5O19, the values of Îµ â€™ = 5.49, while Îµ â€ = 9.35. From the two test materials, it was revealed that in the frequency range of 10 GHz to 15 GHz, absorption did not occur in BaFe12O19, while in BaFe9 (MnCo)1.5Ti1,5O19 absorption occured at 13.0 GHz.Keywords: Ferromagnetic, S-parameter, complek permittivity